Does the incidence of infectious endocarditis show seasonal patterns? — a single center retrospective study - Tofilska, Anna; Zięba, Katarzyna; Surdacki, Andrzej; Rajzer, Marek; Olszanecka, Agnieszka (Folia Medica Cracoviensia, 2023)
Introduction: Seasonal variation has been observed for bacterial and viral infections (e.g., COVID-19 [1]), but also for numerous cardiac problems. However, little information is available on the seasonality of infectious endocarditis (IE), a rare disease that is usually linked to a bacterial origin. Data from the Polish population are lacking. Materials and Methods: Our retrospective study focused on the identification of patients with IE, who were hospitalized at the University Hospital in Krakow between 2005–2022. For this purpose, we searched the medical records system using the ICD-10 code. We decided to divide our patients into four groups (winter, spring, summer, autumn), based on the date of admission to the hospital. Comparison of the distribution of IE incidents by season was performed with the ch2 test. Results: One hundred and ten patients were included in the study (median age 62.5 years (range 20–94), 72 men (65.45%)). The left native valve IE was diagnosed in 49% of the patients, the prosthetic valve IE in 16%, the right valve IE in 27% and the implantable cardiac electronic devices IE in 12% of the subjects. The outcomes comprised of cardiac surgery (n = 53), embolism (n = 16), death (n = 15) and metastatic infections (n = 5). No differences in the incidence of IE by season were observed. Conclusions: In the preliminary observation of IE cases of patients admitted to the University Hospital in Krakow, Poland no seasonal pattern of IE was detected. Therefore, IE should be taken into account in the differential diagnosis at any time of the year.
Keywords: infectious endocarditis; IE; seasonality; heart valves; S. aureus